Utilización y desarrollo de software educativo en el proceso de enseñanza aprendizaje en el primer año de bachillerato de la Unidad Educativa Ismael Pérez Pazmiño de la ciudad de Machala a provincia de el Oro durante el año lectivo 2013-2014. - Tejedor Mendieta, Daysi Johana (2014)
The students of the first year of high school of the educational unit Ismael Pérez Pazmiño located in the intersection of the avenue Las Palmeras and general Manuel Serrano, of the city of Machala, province of the Gold, within this field investigation could be investigated Evidence that teachers do not have the necessary cognitive elements to apply and use technological tools.